Peran Panitia Pengawas Pemilu Kecamatan dalam Menjaga Ketertiban Pemilu Ditinjau dari UU Pemilu No 7 Tahun 2017 - Irianto, Kartika Dewi; Mulyani, Fitria; Budiman, Arif; Fitra, Fitra; Arlando, Arlando (Yayasan Tri Edukasi Ilmiah, 2024)
Elections are a means of realizing the will of the people in government and therefore, elections are a demand for people's sovereignty. So, elections are very important so that the will of the people is not disappointed by ensuring that elections are held directly, publicly, freely, secretly, honestly and fairly. A role exists if there is a position, so a role is a dynamic aspect of status or a functional aspect of position. If someone carries out their rights and obligations in accordance with their position, it means that person has carried out their role.